Exploratory analysis of front-line therapies in REVEL: a randomised phase 3 study of ramucirumab plus docetaxel versus docetaxel for the treatment of stage IV non-small-cell lung cancer after disease progression on platinum-based therapy - Garon, Edward B.; Scagliotti, Giorgio Vittorio; Gautschi, Oliver; Reck, Martin; Thomas, Michael; Docampo, Lara Iglesias; Kalofonos, Haralabos; Kim, Joo-Hang; Gans, Steven; Brustugun, Odd Terje; Orlov, Sergey V.; Carter, Gebra Cuyun; et al. (ESMO open, 2020)
Introduction Non-small-cell lung cancer (NSCLC) is a heterogeneous disease. Front-line therapy may affect responses to subsequent treatment regimens, thus influencing second-line therapy decision making. In the randomised phase 3 REVEL study, second-line ramucirumab plus docetaxel (ram+doc) versus docetaxel (doc) improved survival of patients with metastatic NSCLC. We explore efficacy, safety and quality-of-life (QoL) in REVEL based on front-line therapy. - Methods Patients were grouped by specific front-line therapy received. Overall survival (OS), progression-free survival (PFS), objective response rate, safety and QoL were assessed descriptively. Kaplan-Meier estimation and Cox proportional hazards modelling were used; frequencies reported in percentages. - Results Baseline characteristics of 1253 patients were generally well balanced between treatment arms within each front-line therapy subgroup. For patients with non-squamous disease (n=912), induction therapies included platinum-based chemotherapy plus a taxane (n=227; 25%) or pemetrexed (n=449; 49%), with (n=172; 19%) or without bevacizumab. For patients with squamous disease (n=328), induction therapies included platinum-based chemotherapy plus gemcitabine (n=176; 54%) or a taxane (n=69; 21%). A highly selected subgroup (n=127; 14%) received pemetrexed continuation maintenance therapy. Ram+doc improved median OS and PFS versus doc across front-line therapy subgroups, as reflected by HRs ranging from 0.78 to 0.91 and 0.66 to 0.92, respectively, similar to results in the overall intention-to-treat cohort (HRs: 0.86 and 0.76, respectively). High-grade treatment-emergent adverse events of special interest (including neutropenia, febrile neutropenia, leucopenia and hypertension) were generally higher in ram+doc-treated patients relative to doc-treated patients regardless of front-line therapy. No clear differences in safety or QoL were seen across front-line therapy subgroups; outcomes were consistent with those reported in the overall intention-to-treat cohort. - Conclusions Results of this exploratory analysis suggest that second-line ram+doc may be effective regardless of prior treatment with platinum-based chemotherapy plus a taxane, pemetrexed, gemcitabine or bevacizumab. Overall, ram+doc is clinically beneficial across a wide range of patients with metastatic NSCLC who have progressed after various front-line therapies. - Trial registration number NCT01168973.